Students' Learning Independence in The Problem-Based Learning Model - Syehfudin, Aji (Integral (Jurnal Penelitian Pendidikan Matematika), 2024)
This research is motivated by the low learning independence of Grade X Phase E students. The purpose of this study is to describe how students' learning independence is in the problem-based learning model. This type of research uses a descriptive qualitative approach with a learning independence questionnaire as the instrument. The subjects of this study are Grade X Phase E9 students for the 2023/2024 academic year. Based on the data analysis conducted, the results showed that the average percentage of students' learning independence in each aspect is 77%, which falls into the good category. Therefore, it can be concluded that students' learning independence in the problem-based learning model falls into the good category